SISTEM INFORMASI MONITORING KEGIATAN POSYANDU BERBASIS WEB DI KELURAHAN KOTA RATU PADA BALAI PENYULUHAN KELUARGA BERENCANA (BPKB) - Pitha, Stanislaus (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
The problems that occurred at Posyandu Kota Ratu were the use of manuals by cadres in recording activities still in the ledger, as well as delays in reporting activities by some cadres or posyandu officers. To overcome this problem, the goal is realized through the development of a system in the form of a Posyandu monitoring information system in the Kotaratu Village. The method used uses the Waterfall software method. The system development process is carried out using the HTML, PHP, CSS, and JavaScript programming languages, as well as the use of the MySQL database. The results of the development of this program succeeded in overcoming the obstacles that existed at Posyandu Kota Ratu. Thus, it can be concluded that the system that has been developed is effective in helping overcome the problems faced by Posyandu in Kota Ratu Village. Keywords: BKBM, Information System, Posyandu Monitoring, Website